2023
DOI: 10.3390/children10071243
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Levels, Puberty Timing, and Age at Menarche

Abstract: Pubertal development represents the process of physical maturation where an adolescent reaches sexual maturity and attains reproductive function. The effects of vitamin D are mainly mediated by the vitamin D receptor (VDR), which is expressed in almost all body cells, including the ovary and human pituitary gland and animal hypothalamus. Thus, vitamin D has gained great interest as pathogenic factor of pubertal disorders and fertility. This narrative review aimed to provide a broad overview of the available li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 119 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…Puberty is the physiological process whereby adolescents reach sexual maturity and become capable of reproduction. Puberty onset varies naturally among individuals; in addition to genetic and environmental factors, the importance of nutritional factors, such as iron, zinc, calcium, and vitamin D, increases during puberty ( 4 ). 25(OH)D is a key regulator of neuroendocrine and ovarian physiology ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Puberty is the physiological process whereby adolescents reach sexual maturity and become capable of reproduction. Puberty onset varies naturally among individuals; in addition to genetic and environmental factors, the importance of nutritional factors, such as iron, zinc, calcium, and vitamin D, increases during puberty ( 4 ). 25(OH)D is a key regulator of neuroendocrine and ovarian physiology ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, the probability of menarche was twice as high in vitamin D-deficient girls than in girls who were vitamin D sufficient. In girls, vitamin D deficiency has been shown to decrease the age of menarche by ∼10 months compared with that in girls with sufficient vitamin D ( 4 , 22 ). A systematic meta-analysis of six studies showed that vitamin D-deficient individuals were more likely to develop precocious puberty (OR = 2.02 [95% confidence interval 1.65–2.46]) ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations